Literackie formy i gatunki na łamach "Gazety Nowej", "Codziennego Expressu Zachodniego" i tygodnika "Extra" w latach 1990-1994 = Literary forms and genres in "Gazeta Nowa" ("The NewNewspaper"), "Codzienny Express Zachodni" ("The Daily Western Express") and the weekly "Extra", in 1990-1994 - Rudiak, Robert (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
One of the first newspapers to appear in the free Poland was, in the Lubusz Region, "Gazeta Nowa" a private weekly magazine, which began to circulate in Zielona Góra in January 1990. On 1st October 1990, this weekly was transformed into a daily newspaper, and its modified editions appeared in Głogów, Lubin, Gorzów and, from 1992, also Żary. The newspaper quickly gained many journalists wellknown to the local newspaper market, mainly from the competing "Gazeta Lubu-ska" and from Radio Zachód, together with many writers belonging to the Polish Writers` Union and the Polish Writers`Association. It also attracted the young and talented students of journalism, researchers from several regional centers and universities, and initiated co-operation with recognized Polish publicists, popular satirists and graphic artists, as well as with foreign correspondents - among others,from Germany, Russia, the USA and Africa. It quickly became a counterweight to what had been, until then, the only daily in the Lubusz region, "Gazeta Lubuska" (The Lubusz Daily), in circulation from 1952 (as "Gazeta Zielonogórska"). The new daily quickly came to be dominated by commercial articles, as well as pages and columns dedicated thematically to the social life of elites and celebrities, to business, economics, politics, sensationalism, tourism, gardening, practical advice and, eventually, columns devoted to young people and children. A lot of space was dedicated to culture, art, discussions of cultural events in theregion and the city, theatrical spectacles and books by Lubusz-based authors. The newspaper also started to publish poems, and even, in parts, fragments of proseand novels by Lubusz writers. In 1992 the newspaper appeared with a circulation of 60 000 copies and a lengthof 12 pages. Then the owner of the newspaper sold the title to the Poznań press corporation. A year later, the newspaper was renamed as "The Daily Western Express". At the end of July 1994, the newspaper ended its life as a daily. It initially returned to circulation in the form of a weekly magazine, under the title "Extra", but this failed to meet the expectations of readers, and in September 1994 it was liquidated.
Keywords: prasa; prasa codzienna; tygodniki; gatunki literackie; Gazeta Nowa (czasopismo); Codzienny Express Zachodni (czasopismo); Ekstra (czasopismo); press; daily press; weekly magazines; literary genres